Pregnant individuals perspectives towards receiving COVID-19 vaccination during their pregnancy: an in-depth qualitative study - Sanne J. M. Zilver; Sanne J. M. Zilver; Anna L. Rietveld; Anna L. Rietveld; Noralie N. Schonewille; Noralie N. Schonewille; Petra C. A. M. Bakker; Petra C. A. M. Bakker; Birit F. P. Broekman; Birit F. P. Broekman; Birit F. P. Broekman; Elisabeth van Leeuwen; et al. (Frontiers Media S.A., 2024)
IntroductionPregnant individuals have an increased risk of severe illness from coronavirus disease 2019 (COVID-19) infection. Vaccination is an effective strategy to prevent severe illness and complications for pregnant individuals. Pregnant individuals are often excluded from research and remain hesitant to receive vaccination against COVID-19. It is pivotal to study factors related to vaccine uptake and hesitancy among pregnant individuals. We studied barriers and facilitators for pregnant individuals choice and motivation regarding vaccination against COVID-19 during pregnancy to aid future pregnant individuals in their decision to vaccinate against various infectious agents.MethodsIn this qualitative study, pregnant individuals were interviewed between October 2021 and January 2022 using a semi-structured approach. A topic list was used to explore their feelings, perceptions and ideas regarding vaccination against COVID-19 during pregnancy. Interviews were transcribed verbatim and thematic analyses was performed using MAX QDA.ResultsAfter nine interviews, saturation was reached. Three main themes were identified that influenced pregnant individuals choice and motivation regarding vaccination: health consequences, ambiguity of information and societal motivation. Health consequences mainly concerned the effect for their offspring, and the unknown long-term effects of COVID-19 vaccination. The advice from the Dutch institute for Public Health and Environment changed from not vaccinating pregnant individuals after release of the developed vaccine, to routinely vaccinating all pregnant individuals after research data were available from the United States of America (USA). This change of policy fuelled doubt and confusion for vaccination. Arguments in favor of vaccination from the social perspective were specific behaviour rules and restrictions due to the pandemic. E.g. without vaccination people were unable to travel abroad and having to take a COVID-19 test every time entering a public place.ConclusionPregnant individuals need clear, unambiguous information concerning health consequences, short- and long-term, particularly for their offspring, in the decision-making process regarding COVID-19 vaccination. Additionally, the societal perspective needs to be addressed. Besides the aforementioned themes, general counselling should focus on misperceptions of vaccine safety and the role of misinformation which are also important in the non-pregnant population. This study underlines the importance of including pregnant individuals in research programs to obtain specific information targeted to their needs.